钛合金车削中的低温喷雾射流冷却技术 - 王远 (Jixie chuandong)
The cryogenic mist jet cooling technology is applied to turning process of TC4 titanium alloy which uses cryogenic mist jet with pure water and cryogenic gas as cooling substance.And it is compared with the cryogenic cold wind cooling technology and the normal pouring cooling technology in the same experiment parameters.The experiment result shows:The cryogenic mist jet cooling technology has better cooling effects than other two cooling technology,so this is very significative to improve cutting performances of difficultly machining materials such as titanium alloy.